2018
DOI: 10.1017/s0950268818000614
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological factors and respiratory syncytial virus seasonality in subtropical Australia

Abstract: Evidence is emerging regarding the influence of meteorological factors on seasonal respiratory syncytial virus outbreaks. Data however, are limited for subtropical regions, especially in the southern hemisphere. We examined whether meteorological data (daily minimum and maximum temperatures, rainfall, relative humidity, dew point, daily global solar exposure) and tourist numbers were associated with the incidence of RSV in children aged <5 years for the Gold Coast region of South-East Queensland, Australia (la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…In temperate climates, RSV detection rates were positively associated with relative humidity. 16,18,21 However, some studies undertaken in tropical and subtropical areas have found a positive association with relative humidity, 12,22,23 while others have found a negative association. 11,20,24 Based on the LASSO model, we found that the RSV detection rate was higher when average relative humidity was low.…”
Section: Discussionmentioning
confidence: 99%
“…In temperate climates, RSV detection rates were positively associated with relative humidity. 16,18,21 However, some studies undertaken in tropical and subtropical areas have found a positive association with relative humidity, 12,22,23 while others have found a negative association. 11,20,24 Based on the LASSO model, we found that the RSV detection rate was higher when average relative humidity was low.…”
Section: Discussionmentioning
confidence: 99%
“…However, a shift in the HRSV epidemic season to summer periods (from June-August) has been reported in Japan more recently [4]. Although many previous studies looked at the association between HRSV cases and meteorological conditions [3,[5][6][7][8][9][10][11], there may well be other factors that determine the onset week of HRSV epidemic season.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonality is a feature of many infectious diseases of public health importance and is characterized by case number surges corresponding to predictable calendar periods or some other time related pattern . Annual peaks in influenza, meningococcal disease and pneumonia are well known to result from a complex interplay between host, pathogen and environment with temperature, air quality and relative humidity playing a critical role . Recently, a growing body of literature has come to suggest that post‐operative orthopaedic infections may exhibit seasonal oscillations peaking at times of higher temperature.…”
Section: Introductionmentioning
confidence: 99%